Destabilization of the Tumor-Inducing Plasmid from an Octopine-Type Agrobacterium tumefaciens Lineage Drives a Large Deletion in the Co-resident At Megaplasmid. Issue 10 (1st October 2019) - Barton, Ian S; Platt, Thomas G; Rusch, Douglas B; Fuqua, Clay
Abstract: Bacteria with multi-replicon genome organizations, including members of the family Rhizobiaceae, often carry a variety of niche-associated functions on large plasmids. While evidence exists for cross-replicon interactions and co-evolution between replicons in many of these systems, remarkable strain-to-strain variation is also observed for extrachromosomal elements, suggesting increased genetic plasticity. Here, we show that curing of the tumor-inducing virulence plasmid (pTi) of an octopine-type Agrobacterium tumefaciens lineage leads to a large deletion in the co-resident At megaplasmid (pAt). The deletion event is mediated by a repetitive IS-element, IS66, and results in a variety of environment-dependent fitness consequences, including loss of independent conjugal transfer of the plasmid. Interestingly, a related and otherwise wild-type A. tumefaciens strain is missing exactly the same large pAt segment as the pAt deletion derivatives, suggesting a similar event over its natural history. Overall, the findings presented here uncover a novel genetic interaction between the two large plasmids of A. tumefaciens and provide evidence for cross-replicon integration and co-evolution of these plasmids.